2022
DOI: 10.1093/jnci/djac008
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Advanced Breast Cancer Risk Prediction Model Developed in a Screening Mammography Population

Abstract: Background Estimating advanced breast cancer risk in women undergoing annual or biennial mammography could identify women who may benefit from less or more intensive screening. We developed an actionable model to predict cumulative six-year advanced cancer (prognostic pathologic stage II or higher) risk according to screening interval. Methods We included 931,186 women aged 40-74 years in the Breast Cancer Surveillance Consor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 54 publications
1
53
0
Order By: Relevance
“…These risk estimates can be used by policy makers in conjunction with estimates of other breast cancer screening outcomes (such as cumulative risk of false-positive mammography results and advanced cancer) when evaluating the balance of screening benefits and harms by screening interval. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These risk estimates can be used by policy makers in conjunction with estimates of other breast cancer screening outcomes (such as cumulative risk of false-positive mammography results and advanced cancer) when evaluating the balance of screening benefits and harms by screening interval. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies 13 , 15 , 27 , 42 have identified risk groups that can undergo biennial screening with little adverse change in risk of advanced cancer or life-years gained compared with annual mammography. Our results indicate that women who have low advanced cancer risk with biennial screening (eg, women with healthy weight and nondense breasts) 15 would also experience reduced cumulative DCIS detection with a biennial vs annual screening interval. Of note, risk of screen-detected DCIS on a single screening round was higher with increasing time since last mammography, reflecting the longer interval for DCIS to emerge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a major issue in healthcare. As a result, early identification of breast cancer can lower the risk of patient death [4].…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used method for breast cancer diagnosis is breast imaging medical examination [3,4]. The widely used medical breast images are Mammography [5], Positron Emission Tomography (PET) [6], Magnetic Resonance Imaging (MRI) [7], Computed Tomography (CT) [8] and Ultrasound [9]. Mammography is one of the most widely used screening methods for breast cancer [10,11] due to its low cost, better sensitivity and specificity for breast lesions, and excellent ability to detect lesions of the breast in the early stage of breast cancer [12].…”
Section: Introductionmentioning
confidence: 99%